2003
DOI: 10.1007/s00464-002-8900-0
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic evaluation for peripheral pulmonary nodules during video-assisted thoracoscopic surgery

Abstract: Sonographic guidance during VATS is helpful for locating lesions and determining the extent of surgical resection. The color Doppler method was also useful for evaluating intratumoral blood flow, which yielded significant information for differentiating primary lung cancer, metastatic tumors, and various benign tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 7 publications
1
10
0
Order By: Relevance
“…First, we congratulate them for the results they obtained in their study. We agree with author of the article [4] about the utility of intraoperative sonographic for locating peripheral pulmonary nodules. In our department, we have performed intrathoracoscopic localization of solitary pulmonary nodules.…”
supporting
confidence: 79%
“…First, we congratulate them for the results they obtained in their study. We agree with author of the article [4] about the utility of intraoperative sonographic for locating peripheral pulmonary nodules. In our department, we have performed intrathoracoscopic localization of solitary pulmonary nodules.…”
supporting
confidence: 79%
“…In fact, the lesion appears as homogeneous and hypoechoic, with sonographic disappearance of the hyperechoic pulmonary surface, whereas heterogeneous echogenicity of the lesion is due to air bronchogram or the presence of different tissue or hamartoma [57,66,67]. Moreover, Doppler use can help define the pathology of the pulmonary nodule [82]. However, the ultrasound pattern of the nodules does not distinguish between malignant and benign lesions.…”
Section: Discussionmentioning
confidence: 96%
“…Several perspective studies have shown that the intrathoracoscopic US technique is, in experienced hands, very sensitive and shows a good percentage of nodule localization, ranging from 70 to 100% [10,18,21,36,38,53,57,62,66,67,82]. The number of patients included in these series is low (average <20 patients per study), with the highest being 35 patients in the study by Piolanti et al [53].…”
Section: Noninvasive Intraoperative Techniquesmentioning
confidence: 92%
“…Despite the success describes by the aforementioned studies, one main drawback to this technique is the need for near-complete deflation of the lung to improve the resolution of the images. Although most studies report the actual ultrasound procedure time to be quite low, the time to deflate the lung can be quite lengthy in patients with emphysematous lungs, and many patients who have small pulmonary nodules fall into this group (41,42). In one series, ultrasonography wasn't attempted until the lung had been excluded from ventilation for at least 40 min (43).…”
Section: Discussionmentioning
confidence: 99%
“…Also, there is a learning curve associated with use of the ultrasound equipment, with some studies reporting the presence of a radiologist in the operating room (38,43,44). Suggestion has been made that nodules can be diagnosed based on their ultrasonographic characteristics, but more work must be done in this area (41,45).…”
Section: Discussionmentioning
confidence: 99%